Réponses

2014-01-12T18:43:27+01:00
Bonsoir
1) développer 
f(x) = (2x - 3)² - 5(x+5)( -4x + 6)
f(x) = 4x² - 12x + 9 - (5x+25)(-4x+6)
f(x) = 4x²-12x+9 - ( -20x²+30x-100x+150)
f(x) =4x² - 12x + 9 + 20x² +70x -150 
f(x) = 24x² + 58x - 141 
2) factoriser
f(x) = (2x - 3)² - (5(x+5)(-2)(2x-3))
f(x) = (2x-3)² - (2x-3)(-10x-50)
f(x) = (2x-3)(2x - 3 +10x + 50)
f(x) = (2x - 3) ( 12x + 47) 
3)
f(V2) = 24(V2)² +58(V2) -141 
f(V2) = -93 + 58V2 
f(3/2) = 0 car 2(3/2) - 3  = 0    d'après forme factorisée de f(x)  
f(0) = 24(0)²+58(0)-141 = -141 
f(x) = -141  pour x = 0 
f(x) = 0  si un produit est nul   soit    2x-3 = 0  pour x = 3/2  
                                                     12x+47 = 0  pour x = -47/12 
f(x) = 58x-93  pour x = V2